The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1980
DOI: 10.1002/jcp.1041050221
|View full text |Cite
|
Sign up to set email alerts
|

A hemopoietic cell line dependent upon a factor in pokeweed mitogen‐stimulated spleen cell conditioning medium

Abstract: A continuously growing cell line (FMP1.1) has been isolated, which is dependent upon a factor in PWCM for both growth and survival. FMP1.1 appears to be a mast cell, since IgE receptors are present and their granules react specifically with a mast cell granule stain. The factor in PWCM may be a glycoprotein and has biochemical properties in common with PWCM factors, which stimulate at least four other lineages of hemopoietic colony-forming cell. This line provides a pure population of cells as a model for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Therefore, some morphologically identifiable mast cells in the peritoneal cavity may function as the mast cell precursors. Since peritoneal mast cells appear to float in the fluid, the proliferative potentiality of some peritoneal mast cells reminds us of the suspension culture system of mast cell-like cells that has been devised in many laboratories (41)(42)(43)(44)(45)(46). However, mitosis of peritoneal mast cells is seldom observed in intact animals (10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some morphologically identifiable mast cells in the peritoneal cavity may function as the mast cell precursors. Since peritoneal mast cells appear to float in the fluid, the proliferative potentiality of some peritoneal mast cells reminds us of the suspension culture system of mast cell-like cells that has been devised in many laboratories (41)(42)(43)(44)(45)(46). However, mitosis of peritoneal mast cells is seldom observed in intact animals (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thymic-dependent proliferation of mast cells also occurs in the mucosa of helminth-infected mice (16), and mouse hematopoietic stem cells cultured in vitro in the presence of lymphocyte conditioned medium differentiate into mast cells resembling the mucosal mast cell subclass (17)(18)(19)(20)(21)(22). The cultured cells depend on the T-cell lymphokine interleukin 3 for growth (23) and contain an oversulfated chondroitin sulfate proteoglycan, termed chondroitin sulfate E proteoglycan (24).…”
mentioning
confidence: 99%
“…The culture system that was used in this study pro vided a connective tissue microenvironment for mast cell differentiation so that lesser concentrations of lymphoid or bone marrow cells were plated as com pared to other systems which lacked monolayers [10,16,17,20,22,25], The embryonic skin monolayers, which can contain over 1% mast cells in the starting trypsinates, were grown and subcultured at low plat ing densities to avoid monolayer mast cell contamina tion. Using this culture system, we have obtained evi dence that T cells or T cell products can both enhance or suppress the differentiation or proliferation of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based partly on these early in vitro studies [6,8,12] as well as in vivo studies of a T celldependent, Nippostrongylus brasiliensis (Nb)-induced intestinal mastocytosis [15,18], Burnet [3] suggested that there were two mast cell types: one which devel oped from postmitotic T cells accumulating at sites of immune response such as helminth-infected gut and the other represented by the more typical mast cells characteristic of murine connective tissues and serous spaces. However, it became clear from many subsequent in vitro studies that T cells were required not as precursors but as inducers since T cell super natants could fulfill the T cell requirement [10,16,17,20,22,25]. Alternatively, the in vivo work of Kitamura et al [13] suggested that many mast cell types required no T cell influence for differentiation.…”
Section: Introductionmentioning
confidence: 99%